NiMoFe nanoparticles@MoO2 nano-pillar arrays as bifunctional electrodes for ultra-low-voltage overall water splitting. Issue 7 (25th January 2022) - Liu, Peng; Pan, Weisheng; Yao, Rui; Zhang, Lihan; Wu, Qianyuan; Kang, Feiyu; Fan, Hong Jin; Yang, Cheng
Abstract : A bifunctional alkaline water splitting electrode material featuring dense ternary NiMoFe alloy nanoparticles anchored on the hierarchical MoO2 nano-pillar arrays is prepared by a unique reductive annealing-induced phase separation method. Abstract : Developing advanced bifunctional water splitting electrodes that can perform both hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) is critically important for sustainable hydrogen production because of the simplicity in implementing the system where only one type of electrode material is required. However, the cell voltage of currently available electrolyzers using bifunctional electrodes is still high because maintaining high intrinsic OER and HER activity simultaneously while keeping good charge and mass transport is a challenging task. Herein, the dense ternary NiMoFe alloy nanoparticles are in situ precipitated on the highly conductive hierarchical MoO2 nano-pillar arrays (NiMoFe NPs@MoO2 NPAs) to form an ultra-hydrophilic and super-aerophobic structure by the reductive annealing process-induced phase separation method. Benefiting from the intrinsically high OER and HER activity, abundant active sites and excellent charge and mass transport, the as-obtained NiMoFe NPs@MoO2 NPAs exhibit ultra-low overpotentials of 79 mV for hydrogen evolution and 246 mV for oxygen evolution at 100 mA cm −2 . The assembled two-electrode cell delivers the industrially relevant current densities of 100 and 1000 mA cm −2 at record low cell voltages of 1.52 and 1.66 V while maintaining an almost unchanged potential over 1000 h water splitting. The present method of in situ constructing multielement alloy nanoparticles on hierarchical structure also shows great simplicity and broad applicability potential for preparing high-performance electrocatalysts beyond water splitting.